Anti-corrosion treatment process for ship lock steel structure

By using graphene to modify the combined coating of zinc powder, super epoxy paint and polyurethane coating on the lock steel structure, the construction inconvenience and corrosion risks brought about by traditional zoning design are solved, and a unified long-term anti-corrosion effect is achieved.

CN120502481APending Publication Date: 2025-08-19CCCC SECOND HARBOR CONSULTANTS CO LTD +1

Patent Information

Application Number
CN202510654374.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-21
Publication Date
2025-08-19

AI Technical Summary

Technical Problem

Traditional lock anti-corrosion schemes require zoning design, resulting in inconvenience in construction, difficulty in quality management, and risk of corrosion, especially at regional junctions.

Method used

Anticorrosion coatings containing graphene modified zinc powder are used as primer, super strong epoxy paints are used as intermediate paints, and polyurethane paints are used as topcoats to form a unified anticorrosion coating system, suitable for alternate areas on water, underwater and dry and wet areas.

Benefits of technology

Long-term corrosion prevention in all areas is achieved, inconvenience of zoning construction is avoided, adhesion, water resistance and UV resistance are improved, and construction costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120502481A_ABST
    Figure CN120502481A_ABST
Patent Text Reader

Abstract

The invention relates to an anti-corrosion treatment process for a ship lock steel structure. The anti-corrosion treatment process comprises the steps that S1, the surface of the ship lock steel structure is pretreated; s2, the surface of the pretreated steel structure is coated with an anti-corrosion coating containing graphene modified zinc powder to serve as primer; s3, the surface of the primer is coated with super-strong epoxy paint, intermediate paint is formed, and the super-strong epoxy paint is amine adduct cured high-solid epoxy finish paint; s4, the surface of the intermediate paint is coated with a polyurethane coating to serve as finish paint; by selecting proper paint as primer, intermediate paint and finish paint, one scheme is suitable for all areas and can resist corrosion for a long time, and finally the problem that different areas need to be constructed in different areas is solved. According to the anti-corrosion scheme, the adhesive force is high, the shielding property is high, the water resistance is good, and the ultraviolet resistance is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of anti-corrosion, and in particular relates to an anti-corrosion treatment process for a ship lock steel structure. Background Art

[0002] The traditional anti-corrosion scheme for ship locks is basically designed with reference to the SL105-2007 Anti-corrosion Code for Hydraulic Metal Structures. The anti-corrosion schemes for different areas are different. Long-term anti-corrosion is usually designed in different areas, such as: above-water area: epoxy zinc-rich paint + epoxy intermediate paint + fluorocarbon / polyurethane paint for anti-corrosion; dry-wet alternating area: epoxy zinc-rich paint + epoxy intermediate paint + chlorinated rubber topcoat; underwater area: ultra-thick solvent-free wear-resistant epoxy paint, or thermal spray zinc + coating for anti-corrosion.

[0003] Although this zoning anti-corrosion design scheme is based on the different requirements of each area and combines the characteristics of the environment to achieve the best anti-corrosion effect in each area, the zoning design brings great inconvenience to the anti-corrosion coating process, making construction and quality management inconvenient. In particular, the potential difference at the junction of the areas due to different coating schemes increases the risk of corrosion. Summary of the Invention

[0004] Based on the shortcomings of existing ship lock anti-corrosion solutions, the purpose of the present invention is to provide a ship lock steel structure anti-corrosion solution that is applicable in all areas and can achieve long-term corrosion protection.

[0005] The specific technical solutions of the present invention are as follows:

[0006] The present invention provides an anti-corrosion treatment process for a ship lock steel structure, comprising the steps of:

[0007] S1 pre-treats the surface of the lock steel structure.

[0008] S2 applies an anti-corrosion coating containing graphene-modified zinc powder as a primer on the pretreated steel structure surface.

[0009] The anti-corrosion coating containing graphene-modified zinc powder consists of a first component and a second component, wherein the first component consists of the following components in parts by weight: 12-20 parts of an organic solvent I; 0.5-1.5 parts of a dispersant; 2-4 parts by weight of titanium dioxide; 3-5 parts by weight of talc; 3-5 parts by weight of feldspar powder; 15-25 parts by weight of an epoxy resin; 30-50 parts by weight of graphene-modified zinc powder; 1-3 parts by weight of polyamide wax; and 0.5-2 parts by weight of organic bentonite. The dispersant is KH570.

[0010] The second component consists of the following components in parts by weight: 45-60 parts by weight of polyamide resin, 25-40 parts by weight of organic solvent II, 2-5 parts by weight of silane coupling agent, and 0.5-3 parts by weight of curing accelerator DMP-30.

[0011] The graphene-modified zinc powder is prepared by dispersing a graphene material in an organic solvent (III) to form a graphene material dispersion, then adding zinc powder and grinding the mixture at a temperature below 50°C until the slurry particle size reaches 25 to 35 μm. The anti-corrosion coating containing the graphene-modified zinc powder exhibits excellent rust resistance, water resistance, and strong adhesion. As a primer, it exhibits good adhesion and is not prone to falling off.

[0012] S3 applies super epoxy paint on the surface of the primer to form an intermediate paint. The super epoxy paint is a high-solid epoxy topcoat cured by amine adduct, has good adhesion, tough paint film, good impact resistance, wear resistance, seawater resistance, and crude oil resistance, and has excellent anti-rust effect and good mechanical properties; the shielding effect is very strong to better protect the primer.

[0013] S4: applying polyurethane coating as topcoat on the surface of the intermediate paint.

[0014] The polyurethane coating comprises component A and component B;

[0015] Component A is composed of the following components in parts by weight: 10-30 parts of solvent, 2-8 parts of diformate, 45-75 parts of polyol resin, 0.5-4 parts of modified graphene oxide, 15-35 parts of titanium dioxide, 0.1-1 parts of polyamide wax, 0.1-1 parts of bentonite, and 0.5-2 parts of additives; component B is an isocyanate curing agent.

[0016] In the component A, the solvent is a mixed solution of butyl ester and xylene, the polyol resin is an acrylic acid-modified polyol resin, and the auxiliary agent can be at least one of a leveling agent, a dispersant, and a defoaming agent.

[0017] The modified graphene oxide is prepared by the following method: dispersing graphene oxide in an organic solvent, then adding a silane coupling agent to the obtained graphene oxide dispersion, and reacting at 70-90° C. to obtain the modified graphene oxide; the silane coupling agent is γ-aminopropyltriethoxysilane; and the organic solvent is a mixed solution of xylene and n-butanol or N,N-dimethylformamide.

[0018] The auxiliary agent can be a cationic surfactant: for example, hexadecyltrimethylammonium bromide (CTAB), which can interact with the negatively charged graphene surface to achieve dispersion.

[0019] In the B component, the isocyanate curing agent is any one of toluene diisocyanate, diphenylmethane diisocyanate or isophorone diisocyanate, or a combination of at least two thereof. The amount of curing agent used is generally between one-half and one-quarter of the weight of the resin.

[0020] The polyurethane coating has excellent UV resistance and gloss and color retention.

[0021] The anti-corrosion solution of the present invention uses an anti-corrosion coating containing graphene-modified zinc powder as a primer, a polyurethane coating as a topcoat, and an ultra-strong epoxy paint as a shield between the primer and the topcoat. The solution can be applied above water, underwater, and in alternating wet and dry areas, has strong applicability, is easy to construct, and has low cost.

[0022] The ship lock steel structure described in the present invention is not limited to ship locks, but includes various steel structures in water transport environments, including but not limited to ship locks, fences, lock ingots, etc.

[0023] In some embodiments, the coating thickness of the primer is 60 to 160 microns; the coating thickness of the super epoxy paint is 60 to 200 microns; and the coating thickness of the topcoat is 60 to 120 microns.

[0024] For the anti-corrosion coating whose primer contains graphene-modified zinc powder, the preparation method can be: mixing the components constituting component A and the components constituting component B respectively, and mixing component A and component B in proportion when using and dispersing them evenly.

[0025] In some embodiments, in the anti-corrosion coating whose primer contains graphene-modified zinc powder, the silane coupling agent is a silane coupling agent containing amino and oxygen groups, preferably, coupling agent Z-6011.

[0026] In some embodiments, the mass ratio of component A to component B is 7:1-12.5:1, preferably 10:1.

[0027] In some embodiments, in an anti-corrosion coating having a primer containing graphene-modified zinc powder, the organic solvents I, II, and III are all mixed solutions of xylene and n-butanol; preferably, the mass ratio of xylene to n-butanol is 2.5-4:1. In some preferred embodiments, the mass ratio of xylene to n-butanol is 4:1.

[0028] In some embodiments, in an anti-corrosion coating whose primer contains graphene-modified zinc powder, during the preparation of the graphene-modified zinc powder, the graphene material accounts for 12%-17% of the total weight of the graphene material dispersion, and the mass ratio of graphene material to zinc powder is 2.5:1 to 3.5:1;

[0029] For the topcoat polyurethane coating, its preparation method can be to mix the ingredients constituting component A, mix component A with component B when using, cure at room temperature, and maintain at 25°C for more than 7 days to obtain the polyurethane coating.

[0030] In some embodiments, in the polyurethane coating, the mass ratio of component A to component B is 3:1-9:1.

[0031] In some embodiments, in the polyurethane coating, in the solvent of component A, the mass ratio of butyl ester:xylene is 2:1-5:1; preferably, the mass ratio of butyl ester:xylene is 3:1.

[0032] In some embodiments, for the preparation of modified graphene oxide in polyurethane coating, the silane coupling agent is silane coupling agent Z-6011.

[0033] In some embodiments, for the preparation of modified graphene oxide in polyurethane coating, graphene oxide is dispersed in an organic solvent by ultrasonic dispersion to prepare a graphene oxide dispersion. Preferably, the ultrasonic dispersion time is 10-40 min.

[0034] In some embodiments, for the preparation of modified graphene oxide in polyurethane coating, the graphene oxide concentration in the graphene oxide dispersion is 0.01 to 0.1 g / mL.

[0035] In some of the embodiments, for the preparation of modified graphene oxide in polyurethane coating, the reaction time of the silane coupling agent and graphene oxide is 5 to 24 hours.

[0036] For super-strong epoxy coatings used as intermediate paints, high-solid epoxy coatings cured by amine adducts can be selected, such as HBG-D-2 super-strong epoxy paint from Haobang Graphene New Materials Technology Co., Ltd., epoxy intermediate paint from Tianlang Chemical, and epoxy ship paint from Zhejiang Yutong New Materials Co., Ltd.

[0037] The beneficial effects of the present invention are:

[0038] Compared with the prior art, the present invention, by selecting appropriate coatings for the primer, topcoat, and midcoat, avoids the problems of existing solutions, such as the use of zinc-containing primers in underwater areas with cathodic protection and impressed current, as well as the water and wear resistance of polyurethane coatings, as well as their blistering underwater. This single solution is applicable to all areas and provides long-term corrosion protection, ultimately resolving the need for zoning construction in different areas. The anti-corrosion solution of the present invention boasts an adhesion of up to 22 MPa (compared to the conventional 6-8 MPa), strong shielding properties, excellent water resistance, and UV resistance of over 4000 hours, making it suitable for use in water transport environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Schematic diagram of the test results of different anti-corrosion combinations in Example 3.

[0040] Figure 2 This is a picture of the actual engineering application scenario of the anti-corrosion process of the present invention. DETAILED DESCRIPTION

[0041] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form.

[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in this specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0043] Unless otherwise specified, the reagents, materials, and equipment used in the examples of the present invention are all commercially available; and the experimental methods, unless otherwise specified, are all conventional experimental methods in the art.

[0044] in,

[0045] Epoxy resin E-44: industrial grade, Baling Petrochemical Co., Ltd.

[0046] Xylene and n-butanol, analytical grade, Sinopharm;

[0047] Zinc powder: 325 mesh, Jiangsu Kecheng Company;

[0048] γ-Aminopropyltriethoxysilane: Hangzhou Jessica Chemical Co., Ltd.;

[0049] Graphene material: Changzhou Sixth Element Co., Ltd.;

[0050] Feldspar powder: Guangzhou Jialiang Mineral Products Co., Ltd.

[0051] Talc: Guangzhou Jialiang Mineral Products Co., Ltd.

[0052] Polyamide wax: Jintenglong Industrial;

[0053] Organic bentonite: Jintenglong Industrial.

[0054] Test method:

[0055] Adhesion test: The standard "Determination of adhesion of coatings - Pull-off method" (GB / T 5210) was used; Salt spray resistance test: The standard "Paints and varnishes - Determination of resistance to neutral salt spray" (GB / T 1771) was used;

[0056] Cathodic disbonding resistance test: cathodic disbonding resistance of the sample plate is tested using Method B in the standard "Paints and varnishes - Test for resistance to cathodic disbonding of coatings exposed to seawater" (GB / T 7790);

[0057] Xenon lamp aging resistance test: Adopt the standard "Paints and varnishes - Artificial weathering and artificial radiation exposure to filtered xenon arc radiation" (GB / T 1865);

[0058] Potential resistance performance test: Adopt the standard "General Technical Conditions for Anode Screen Coatings for Ships and Marine Engineering"

[0059] (GB / T 7788);

[0060] Moisture and heat resistance test: Adopt the standard "Determination of moisture and heat resistance of paint film" (GB / T 1740);

[0061] Environmental spectrum test: Adopt the standard "Paints and varnishes - Corrosion protection of steel structures by protective coating systems Part 9: Protective coating systems for offshore structures and related structures and laboratory performance test methods"

[0062] Environmental spectrum in the cyclic corrosion aging test method in (ISO 12944-9);

[0063] Artificial seawater dry-wet cycle test: immerse the sample in artificial seawater at 23℃ for 4 hours, then take it out and air it at 23℃ for 8 hours, and repeat this cycle for 6 months;

[0064] Freshwater wet-dry cycle test: Immerse the sample in deionized water at 23℃ for 4 hours, then take it out and air it at 23℃ for 8 hours. Repeat this cycle for 6 months.

[0065] Example 1: Preparation of a primer containing graphene-modified zinc powder as an anti-corrosion coating

[0066] 1.1 Preparation of graphene-modified zinc powder

[0067] (1) 150 g of a graphene material having a specific surface area of 180 to 220 m2 / g is dispersed in 1000 g of an organic solvent to prepare a graphene material dispersion, wherein the graphene material accounts for 15% of the total weight of the graphene material dispersion; the organic solvent is a mixed solvent of xylene and n-butanol, wherein the mass ratio of xylene to n-butanol is 3:1.

[0068] (2) adding 60 g of zinc powder to the graphene material dispersion, stirring at 1200 rpm for 30 min to obtain a crude product;

[0069] (3) Grinding the crude product and controlling the temperature to be kept below 60° C. to obtain graphene-modified zinc powder with a particle size of 25-35 μm.

[0070] 1.2 Preparation of anti-corrosion coating

[0071] (1) Preparation of coating component A

[0072] Add the formulated amount of xylene, n-butanol, and dispersant to the container, use a disperser to maintain a speed of about 300 rpm to evenly disperse, then add the formulated amount of epoxy resin, polyamide wax, graphene-modified zinc powder, titanium dioxide, talc, feldspar powder, and organic bentonite in sequence and disperse evenly;

[0073] (2) Preparation of coating component B

[0074] The curing agent polyamide 650, solvent, silane coupling agent and curing accelerator in the formula amount are mixed and stirred evenly, wherein the solvent consists of xylene and n-butanol, wherein the mass ratio of xylene to n-butanol is 3:1.

[0075] Table 1 Anti-corrosion coating formula containing graphene modified zinc powder

[0076]

[0077] Example 2 Preparation of Topcoat-Polyurethane Coating

[0078] 2.1 Preparation of modified graphene oxide

[0079] (1) 10 kg of graphene material with a specific surface area of 180 to 220 m2 / g was ultrasonically dispersed in 100 L of organic solvent for 30 min to prepare a graphene material dispersion; the organic solvent was a mixed solvent of xylene and n-butanol, wherein the mass ratio of xylene to n-butanol was 3:1.

[0080] (2) Add 1 kg of γ-aminopropyltriethoxysilane to the graphene material dispersion, stir and react at 80° C. and 1200 rpm for 10 h to obtain modified graphene oxide.

[0081] 1.2 Preparation of anti-corrosion coating

[0082] (1) Preparation of coating component A

[0083] Add the formulated amount of xylene, n-butanol, and dispersant to the container, use a disperser to maintain a speed of about 300 rpm to disperse evenly, then add the formulated amount of acrylic modified polyol resin, polyamide wax, modified graphene oxide, titanium dioxide, bentonite, and additives in sequence and disperse evenly;

[0084] (2) Preparation of coating component B

[0085] Prepare the isocyanate hardener.

[0086] Table 2 Topcoat polyurethane coating formula

[0087]

[0088]

[0089] Example 3 Steel structure anticorrosion experiment

[0090] Refer to Table 3 to preliminarily design various primer, mid-coat and topcoat combinations for anti-corrosion testing. The specific steps include:

[0091] S1 Pre-treat the surface of the steel structure: clean off the oil stains and spray treat until the surface roughness is ≤Sa2.5.

[0092] S2: Component A and component B obtained in Example 1 were mixed in a weight ratio of 10:1, stirred evenly, and sprayed on the pretreated steel structure surface as a primer with a spraying thickness of 60 μm and cured for 24 hours.

[0093] S3: Spray super strong epoxy paint on the primer surface as the intermediate paint; spray thickness 100 microns, and cure for 24 hours;

[0094] S4: Component A and component B obtained in Example 2 were mixed in a weight ratio of 10:1, sprayed on the surface of the intermediate paint as a topcoat with a spraying thickness of 80 μm, and cured for 168 h.

[0095] Table 3 Coating combinations of Examples 3-1 to 3-9

[0096]

[0097] The test results are shown in Table 4. Preliminary experiments show that the primer-intermediate paint-topcoat combinations of the embodiments of the present invention basically meet the anti-corrosion requirements of ship steel structures.

[0098] Table 4 Anticorrosion test results of Examples 3-1 to 3-9

[0099]

[0100] Preliminary results show that the combination of 3-2 has a good effect. A comparative example is set based on 3-2. The specific experimental settings and test results are shown in Table 5. For detailed results, please refer to Figure 1 .

[0101] Table 5 Comparative test results of different anti-corrosion systems

[0102]

[0103]

[0104] According to Table 5 and Figure 1 It can be seen that the primer, intermediate paint and topcoat of the present invention are indispensable and can only achieve better performance by cooperating with each other. Moreover, compared with other solutions, the anti-corrosion coating system of the embodiment of the present invention has excellent adhesion and good durability. Moreover, compared with traditional anti-corrosion solutions (Comparative Examples 5-6), the present invention can achieve better performance at a lower coating thickness.

[0105] Example 4: Anti-corrosion application of ship locks

[0106] 4.1 Comparative Experiment

[0107] The anti-corrosion combination of the embodiment of the present invention was applied to the steel structure environment of the ship lock and compared with the existing steel structure coating. The specific coating experimental system is shown in Table 6 and Table 7. The test results are shown in Table 8.

[0108] Table 6 Test system for coating of traditional ship lock steel structure

[0109]

[0110] Table 7 Test system of anti-corrosion coating for ship lock steel structure according to the embodiment of the present invention in freshwater environment

[0111]

[0112] Table 8 Comparison of test results of conventional steel structure coating and graphene zinc powder coating test system of the present invention

[0113]

[0114] Test results show that the coating system constructed using the present invention's anti-corrosion process can be applied to different areas with the same combination, exhibiting excellent adhesion, minimal corrosion expansion, and superior corrosion resistance. It also exhibits low potential resistance and superior potential resistance. It also offers comparable wet-heat performance, aging resistance, and environmental spectrum resistance to traditional steel structure coating systems.

[0115] 4.2 Engineering Verification

[0116] The comparative experimental results demonstrate that the graphene-zinc powder anti-corrosion coating system constructed using the present invention's anti-corrosion process exhibits superior corrosion protection compared to conventional coating systems for hydraulic steel structures. This graphene-zinc powder anti-corrosion coating system is suitable for corrosion protection of ship lock steel structures. Furthermore, this work has further conducted engineering validation of the graphene-zinc powder anti-corrosion coating system.

[0117] refer to Figure 2 The actual engineering verification was carried out on the gate corrosion protection of the Minjiang Qianwei Navigation and Power Project, the Gezhouba trash rack, and the Three Gorges Power Station lock spindle. During the entire verification process, the construction performance of the present invention was excellent, and the coating was intact without any abnormality during the verification period.

[0118] Table 9 Graphene anti-corrosion coating system engineering verification cases

[0119]

[0120] From the above, it can be seen that the method scheme of the present invention can meet the design requirement of a service life of more than 10 years by adopting a single coating scheme for each area, and the design life can be increased to 20 years by changing the coating thickness.

[0121] The technical features of the above-described embodiments can be combined in any combination. To simplify the description, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention. Therefore, the scope of protection of the patent of this invention shall be based on the attached claims.

Claims

1. A process for anti-corrosion treatment of ship lock steel structure, characterized in that: Including steps: S1 pre-treats the surface of the lock steel structure; S2 applies an anti-corrosion coating containing graphene-modified zinc powder as a primer on the pretreated steel structure surface; The anti-corrosion coating containing graphene-modified zinc powder consists of a first component and a second component, wherein the first component consists of the following components in parts by weight: 12-20 parts of an organic solvent; 0.5-1.5 parts of a dispersant; 2-4 parts by weight of titanium dioxide; 3-5 parts by weight of talc; 3-5 parts by weight of feldspar powder; 15-25 parts by weight of an epoxy resin; 30-50 parts by weight of graphene-modified zinc powder; 1-3 parts by weight of a polyamide wax; and 0.5-2 parts by weight of organic bentonite. The dispersant is KH570. The second component is composed of the following components in parts by weight: 45-60 parts by weight of polyamide resin, 25-40 parts by weight of organic solvent II, 2-5 parts by weight of silane coupling agent, and 0.5-3 parts by weight of curing accelerator DMP-30; The graphene-modified zinc powder is prepared by dispersing the graphene material in an organic solvent III to prepare a graphene material dispersion, then adding zinc powder, and grinding at a temperature below 50° C. until the slurry particle size is 25 to 35 μm. S3: applying a super epoxy paint on the surface of the primer to form an intermediate paint, wherein the super epoxy paint is a high-solid epoxy topcoat cured by an amine adduct; S4: applying polyurethane coating as topcoat on the surface of the intermediate paint; The polyurethane coating comprises component A and component B; Component A is composed of the following components in parts by weight: 10-30 parts of solvent, 2-8 parts of diformate, 45-75 parts of polyol resin, 0.5-4 parts of modified graphene oxide, 15-35 parts of titanium dioxide, 0.1-1 parts of polyamide wax, 0.1-1 parts of bentonite, and 0.5-2 parts of additives; Component B is an isocyanate curing agent; In the component A, the solvent is a mixed solution of butyl ester and xylene, and the polyol resin is an acrylic acid-modified polyol resin; The modified graphene oxide is prepared by the following method: dispersing graphene oxide in an organic solvent, then adding a silane coupling agent to the obtained graphene oxide dispersion, and reacting at 70-90° C. to obtain the modified graphene oxide; the silane coupling agent is γ-aminopropyltriethoxysilane; and the organic solvent is a mixed solution of xylene and n-butanol or N,N-dimethylformamide; In the component B, the isocyanate curing agent is any one of toluene diisocyanate, diphenylmethane diisocyanate or isophorone diisocyanate, or a combination of at least two thereof.

2. The anti-corrosion treatment process for ship lock steel structure according to claim 1, characterized in that: The dry film thickness of the primer is 60 to 160 microns; The dry film thickness of the intermediate paint is 60 to 200 microns; The dry film thickness of the topcoat is 60 to 120 microns.

3. The anti-corrosion treatment process for ship lock steel structure according to claim 1, characterized in that: In the anti-corrosion coating whose primer contains graphene-modified zinc powder, the silane coupling agent is a silane coupling agent containing amino groups and oxygen groups, preferably coupling agent Z-6011.

4. The anti-corrosion treatment process for ship lock steel structure according to claim 1, characterized in that: In the anti-corrosion coating whose primer contains graphene-modified zinc powder, the mass ratio of the first component to the second component is 7:1-12.5:1, preferably 10:

1.

5. The anti-corrosion treatment process for ship lock steel structure according to claim 1, characterized in that: In the anti-corrosion coating whose primer contains graphene-modified zinc powder, the organic solvents I, II, and III are all mixed solutions of xylene and n-butanol; preferably, the mass ratio of xylene:n-butanol is 2.5-4:

1.

6. The anti-corrosion treatment process for ship lock steel structure according to claim 1, characterized in that: In the anti-corrosion coating whose primer contains graphene-modified zinc powder, for the preparation of graphene-modified zinc powder, the graphene material accounts for 12%-17% of the total weight of the graphene material dispersion, and the mass ratio of graphene material to zinc powder is 2.5:1 to 3.5:

1.

7. The anti-corrosion treatment process for ship lock steel structure according to claim 1, characterized in that: In the polyurethane coating used as a topcoat, the mass ratio of component A to component B is 3:1-9:

1.

8. The anti-corrosion treatment process for ship lock steel structure according to claim 1, characterized in that: In the polyurethane coating used as the topcoat, the solvent of component A has a mass ratio of butyl ether:xylene = 2:1-5:1; preferably, butyl ether:xylene = 3:

1.

9. The anti-corrosion treatment process for ship lock steel structure according to claim 1, characterized in that: In the polyurethane coating used as a topcoat, for the preparation of modified graphene oxide, the silane coupling agent is silane coupling agent Z-6011.

10. The anti-corrosion treatment process for ship lock steel structure according to claim 1, characterized in that: In the polyurethane coating, for the preparation of modified graphene oxide, the graphene oxide concentration in the graphene oxide dispersion is 0.01 to 0.1 g / mL.

Citation Information

Patent Citations

  • Graphene modified zinc powder, preparation method and heavy duty anticorrosion paint containing the same

    CN109021622A

  • Water-based epoxy intermediate paint

    CN109337511A

  • Polyurethane coating and preparation method and application thereof

    CN109593454A

  • Anti-corrosion coating system for outer wall of tower drum of marine wind turbine generator and coating method

    CN113150642A

Cited By

  • A weather-resistant and anti-aging protective layer for offshore wind power facilities and its preparation method

    CN122356958A

  • A marine photovoltaic anticorrosive coating composition and a preparation method thereof

    CN122405142A

  • A marine photovoltaic anticorrosive coating composition and a preparation method thereof

    CN122405142B